2014
DOI: 10.3892/mmr.2014.2276
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant promoter DNA methylation inhibits bone morphogenetic protein 2 expression and contributes to drug resistance in breast cancer

Abstract: Bone morphogenetic protein 2 (BMP2) is a growth factor that is involved in the development and progression of various types of cancer. However, the epigenetic regulation of the expression of BMP2 and the association between BMP2 expression and drug resistance in breast cancer remains to be elucidated. The present study reported that the expression of BMP2 was significantly decreased in primary breast cancer samples and the MCF‑7/ADR breast cancer mulitdrug resistance cell line, which was closely associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
1
8
0
3
Order By: Relevance
“…Bone morphogenic proteins are crucial for the development of both the central and peripheral nervous systems in vertebrates, regulating neural stem cell fate and maturation [ 30 , 31 ]. Their roles and regulation in chemo brain and tumor brain need to be further elucidated, especially given the fact that many of the BMP genes are epigenetically regulated via DNA methylation [ 32 ]. Our initial analysis suggested that non-CNS tumor growth led to demethylation of BMP4 promoter in the PFC tissues of tumor-bearing animals as compared to intact ones ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Bone morphogenic proteins are crucial for the development of both the central and peripheral nervous systems in vertebrates, regulating neural stem cell fate and maturation [ 30 , 31 ]. Their roles and regulation in chemo brain and tumor brain need to be further elucidated, especially given the fact that many of the BMP genes are epigenetically regulated via DNA methylation [ 32 ]. Our initial analysis suggested that non-CNS tumor growth led to demethylation of BMP4 promoter in the PFC tissues of tumor-bearing animals as compared to intact ones ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The bottom gene in the list encodes Bone Morphogenetic Protein 2 (BMP2). Promoter DNA methylation of BMP2 contributes to drug resistance in breast cancer [ 20 ]. Another most commonly inactivated gene in various cancers, Ras association domain-containing protein 1, RASSF1 , undergoes either DNA methylation or chromosomal deletion in breast cancer [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Du et al. 64 reported that knockdown of BMP2 increased chemoresistance of the MCF-7 breast cancer cell line. Similarly, Liu et al.…”
Section: Main Textmentioning
confidence: 99%